Potabilização de água eutrofizada utilizando destilação solar - Carvalho, Eyre Katrinne Ferreira de (2015)
This research aimed to evaluate the removal of microcystin-LR and saxitoxin of eutrophic water produced in the laboratory for solar pyramid type still, in order to obtain a drinking water that meets all the potability standards specified in the ordinance 2914 / 11 of the Health Ministry. The methodology for analysis of physical and chemical parameters obeyed preconization the APHA 2012. The analyzes for evaluating the removal cianotoxins were performed by liquid chromatography coupled mass spectrometry (LC/MS) by method has been validated. Experiments were performed with two identical solar stills , the material used for the tray of distillers was stainless steel, simple glass cover and pyramidal geometry, subject to the same climatic conditions and fed two types of study of water (AE), prepared with lysate cultivation of Microcystis aeruginosa and Cylindrospermopsis raciborskii, cyanobacteria were cultivated in the laboratory under controlled conditions and constant monitoring. The solar distillation system had maximum yield of 2,4 L / m².day , less than some similar distillers in the literature, the system can be optimized and this income can be increased from a better insulation system. The results showed for removing turbidity higher than 95% true color was reduced from 20 to 5 uH uH on average, after the distillation process, as expected, there was a decrease in pH and hardness in relation to study water, ammonia showed a slight increase in concentration, but still remained within the maximum amount allowed by law. The results showed initial concentrations in the study of water 11,4 μg.L^-1 and 2 μg.L^-1 for microcystin - LR and saxitoxin respectively, in distilled water was not detected by the method used cyanotoxins . To prove that there has been removing samples were then injected into the mass spectrometer and the results it could be concluded that the cyanotoxins were concentrated in the remaining water from the tray allowing the final result clean water, free of cyanotoxins .